(untitled) (Research in Agriculture Livestock and Fisheries, 2026)
Slaughterhouse examination aids a cost-effective and reliable method for identifying systemic pathologies, providing essential data for livestock disease management and food safety assurance. Here, visceral organs (liver, lungs, spleen) of 10 randomly selected adult Black Bangel goats at the time of normal slaughter were collected to assess gross and histopathological features from a public health perspective. This cross-sectional study was conducted at two slaughterhouses in Mymensingh City Cooperation. Gross pathological examination revealed multisystemic involvement affecting the liver, lungs, and spleen. The liver exhibited marked discoloration, areas of necrosis, and thickened bile ducts, consistent with necrotizing cholangiohepatitis. Pulmonary lesions were observed and were characterized by pale to dark discoloration, congestion, and areas of hepatization. The spleen showed a wrinkled capsule and splenic congestion. Histopathological examination of livers revealed periportal lymphoplasmacytic hepatitis, biliary hyperplasia, and multifocal abscesses with hemosiderosis. Pulmonary lesions were characterized by granulomatous pneumonia with serofibrinous exudates and peribronchial inflammatory infiltration. Additionally, the spleen showed marked lymphoid depletion and trabecular thickening, consistent with chronic splenic atrophy and hemosiderosis. These organ-level changes may result from various infectious and non-infectious etiologies. Based on the gross and histopathological findings, the goats were suspected to be affected by infectious diseases, including Peste des Petits Ruminants (PPR), Tuberculosis, and Fascioliasis. While pathological findings are indicative of infection, molecular or microbiological confirmation is required to substantiate the diagnosis and support broader animal health surveillance and food-safety initiatives. Res. Agric. Livest. Fish. Vol. 13, No. 1, April 2026: 103-116